Control of Aerosolised Type A Influenza Virus H1N1 and a Coronavirus with Vapours Containing Catmint Essential Oil - Muhammad Yasir; Mark D. P. Willcox; John Ings; Peter van Bruinessen (Hygiene)
Background: Respiratory viruses spread through airborne droplets and aerosols, causing highly contagious acute respiratory syndromes in humans. This study evaluated the antiviral potential of vapours of catmint-oil-based formulations against respiratory viruses. Methods: The antiviral activity of formulations with or without catmint oil (CO) in solution or in aerosolised form was determined against influenza virus H1N1 ATCC VR-1469 and mouse hepatitis virus (MHV-1) ATCC/VR261. In solution, both viruses were exposed to CO formulations for 2–3 h. In aerosolised form, H1N1 was exposed to formulations for 2 min in a closed cylinder and MHV-1 for 10 min in a booth. The antiviral effect of the formulations was evaluated by growing H1N1 in a Madin–Darby canine kidney (MDCK; ATCC-CRL-2936) and MHV-1 in A9 ATCC/CCL 1.4 cells using TCID50 and a plaque assay, respectively. Transmission electron microscopy (TEM) was conducted to investigate the mode of action of the formulations. Results: In solution, the formulation containing hydrogenated CO (HCO), bromelain, N-acetylcysteine and Tween 20 (Formulation (1)) reduced the viability of H1N1 by 2.6 ± 0.07 log10 (p = 0.025) and MHV-1 by 4.5 ± 0.14 log10 (p = 0.014) within 2–3 h. In vapourised form, Formulation (1) produced similar antiviral effects against H1N1, reducing it by 3.00 ± 0.07 log10 (p = 0.002) within 2 min, and Formulation (1) produced a 3.00 ± 0.07 log10 reduction of MHV-1 (p < 0.001) within 10 min (the minimum time needed to detect infective viral particles in the experimental set-ups). Formulation (3) (without bromelain) reduced H1N1 by 1.57 ± 0.14 log10 (p = 0.008) after 2 min and MHV-1 by 1.3 ± 0.04 log10 (p = 0.057) after 10 min. In the absence of catmint oil (Formulation (4)) or in the absence of catmint oil and bromelain (Formulation (5)), there were only slight reductions in the viability of aerosolised H1N1 (1.00 ± 0.14 log10, p = 0.046; <1 log10, p = 0.966, respectively) and MHV-1 (1.07 ± 0.02 log10, p = 0.013; 0.16 ± 0.03 log10, p = 0.910, respectively). The TEM analysis showed that the formulation disrupted the H1N1 envelopes and caused a reduction in size of the viral particles. Conclusions: The catmint-oil-based formulations reduced the H1N1 and MHV-1 by disrupting the vial envelopes.